Multifactor authentication as a computer security measure against cyber threats: An approach to be adopted by African countries and companies - (:unkn) unknown (My University, 2024)
Since the digital world has invaded planet Earth and since man is able to communicate remotely with his neighbor from the other end of the world, man becomes vulnerable. Since companies are looking to increase their productivity and potential new customers online, and to house all the company’s related information including its agents, to servers, it becomes vulnerable.In the African continent, the concept of computer security often poses a problem, even its popularization is not yet widespread in some countries and in most of these countries the frequency of computer threats is booming. The African population suffers from the problem of digital extortion, online scams, and many other cyber threats every day.Each year, nearly 90% of African companies are threatened by cyber attacks because these companies’ computer security is not really up to date.Few agents of African companies, schools, universities, and governments are aware in the field of cyber attack or cyber threat. This opens the way for cyber attacks to threaten and scam people while stealing user data. It is advisable that the protection of user data is a top priority for a company and multi-factor authentication is one of the safest ways to verify the identity of customers, agents when they connect to a company’s system or a website. In this article, we will present to you the importance of multi-factor authentication to secure remote access and strengthen security and reduce the risks of attacks and theft of user information in a company’s information system.
Keywords: African Research